New Product Development for Furniture Business (Case Study:Work to Create) - Ramadhan, Fadly Rizky; Dellyana, Dina (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Furniture is an example of a product that naturally lends itself to internationalization in that if performs the same basic function across geographic areas and cultures such as seating, bedding, dining, storage and display (Smith & West, 2008). General head of Himpunan Industri Mebel dan Kerajinan Indonesia (HIMKI), Soenoto, stated that world’s furniture market value currently reach US141 billion, and Indonesia took 1,5% of the value which is worth US1,9 billion. Worktocreate is one of those furniture-making companies, which currently in demand for some of local brands personal need. It fulfills the need not only from local fashion brand but also some of local startups in form of restaurant, event organizer, and even someone’s personal home supplies. It has been a great year for the owner in term of brand recognition but the thing was that it only creates product when the customer need it. In the contrary, they need to become sustainable by having a fixed monthly income. This monthly income led to the urge in creating a product, which fit the market enough to last for years. In order to overcome the problems, some objectives were set which are to analyze what kind offering should worktocreate create to fulfill the market’s demand, to analyze the suitable marketing strategy and business analysis for the product, and to analyze the acceptance of the new product which is developed. This research used semi-structured interview to find out the buyer persona and answered the research objectives. According to the interview, the result is that there two type of buyer persona which are The Impulsive, who like to purchase furniture to just decorate their house, and The Considerate, who really pay attention to a lot of aspects. It is recommended for the owner to offer something multi-function and had minimalistic design. Specifically to attract The Impulsive one, owner should put his furniture product catalog online, which consist of product that has been created and the future design. Another note that the owner should consider putting their product on an event or a wholesale store to gain more brand awareness. Lastly, having a shop is a must because some of market prefer to see the product directly.Keywords: Furniture, Semi-structured Interview, Entrepreneur, New product development, Buyer persona